P-B14 Methylation as a triage marker in a hHPV+ population in Nigeria. (January 2016) - Modibbo, Fatima; Leeman, Annemiek; Iregbu, Kenneth; Kasius, Annemieke; Oluwande, Oluwatoyosi; De Koning, Maurits; Quint, Wim; Adebamowo, Clement
Abstract : Objectives: To assess the feasibility of the Precursor-M methylation test as a triage marker on self-collected and hospital-collected samples amongst a hrHPV+ population in a resource limited setting. Methods: A total of 400 women were invited to participate through flyer recruitment in Abuja, Nigeria. After randomization, 200 were asked to self-collect and deposit cervical samples at designated collection points and 200 were invited to the hospital for a hospital-collected sample (HCS). A dry flocked swab was used in both groups. DNA was isolated with the nucliSENS easyMAG, tested with the GP5+/6+-PCR-EIA. A qPCR (RNaseP) to assess the level of DNA was performed. EIA+ samples with a Cq<28 (human genomic DNA concentration >1 ng/μL) were tested with the Precursor-M methylation kit. Cut-offs for positivity were applied as described by the test manufacturer. Results: Samples from all 298 responding women (74.5% response) were included. The mean age of the women was 41.1 (SD 7.8, range 30–62). A total of 29 samples were found hrHPV+ by GP5+/6+; 28 (96.6%) contained enough DNA for Precursor-M testing (11 HCS, 17 self-samplers). 28.6% (8/28), including 3 HCS and 5 self-samplers, were methylation positive. Conclusions: The percentage of 28.6% methylation positive samples corresponds with previous findings (De Strooper et al, 2014). In order to assess the feasibility of methylation testing as a triage marker in the detection of high grade CIN lesions in an all-molecular screening setting, a follow-up study collecting a colposcopy directed biopsy will be performed. Results are expected by September 2015.